COMMUNITY BUSINESS EXPANSION TO IMPROVE THE ECONOMY THROUGH E-COMMERCE IN THE PANDEMIC ERA (CASE STUDY: PEOPLE OF GUNUNGKIDUL REGENCY) - Khasanah, An Nisa Uswatun; Wahid, Abdurrahman; Siswanto, Siswanto (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
In the era of the COVID-19 pandemic, economies around the world are facing tremendous challenges. Economy is one of the aspects that is swayed at this time, because it has become a pillar of many people's lives, including in Indonesia, especially in Gunungkidul Regency. The survival of MSMEs is one of the pillars of the economy so that it always stays alive. However, it is not necessarily that MSMEs try themselves in this phase. MSMEs are also assisted by technological developments. Researchers in this study used a descriptive qualitative method using the case study method. Using a case study approach, the study allows the reader to see the case of a specific context being investigated through the analysis of data from various sources. The data used is primary data with data collection techniques carried out, namely interviews and discussions with several informants. MSME actors in Gunungkidul Regency became the population in this study. The sample from this study was using purposive sampling techniques. The development of technology is one of the spearheads for MSMEs to survive and experience glory. This research seeks to provide a fundamental picture of how the development of MSMEs through the use of e-commerce during the Covid-19 pandemic. This research is a qualitative research with a survey approach method. Surveys are conducted on informants who are already qualified in this field.